PENERAPAN DATA MINING ALGORITMA APRIORI DALAM MENGGANTI SPARE PART DIES MAINTENANCE UNTUK MENCEGAH POTENSI DIES ACCIDENT PT. NUSA TOYOTETSU CORPORATION - Ucok Darmanto Soer (DPPM Universitas Pelita Bangsa, 2021)
Application of data mining Apriori Algorithm in replacing Spare Parts for Dies Maintenance to prevent potential Dies Accident of PT. Nusa Toyotetsu Corporation. At PT. Nusa Toyotetsu Corporation, in the maintenance of spare parts replacement Dies Maintenace tools still arise various problems. Spare parts should be replaced because the age of the spare parts or their eligibility does not meet production standards, but they are not replaced, because negligence of a Maintenace worker can have an impact on the Dies Accident which can be detrimental to the company. Therefore the authors conducted a data mining research Apriori Algorithm with the Association Rules method so that it can be used for data analysis and processing of Spare Parts Dies Manitenance Replacement, to Prevent the Potential Accident Dies. By determining a minimum Support of 50% and a minimum of 80% Confidence then found 6 rules of association patterns that can be used as a recommendation in replacing Dies Maintenance spare parts. If replacing a WSS 10 spare part, the possibility of CB 10-30 spare parts also needs to be replaced, supported by a Support value of 58% and a Confidence of 86%. If replacing a WSS 10 spare part, the possibility of a WSS 12 spare part also needs to be replaced, supported by a Support value of 58% and a Confidence of 86%. If replacing CB 8-20 spare parts, the possibility of MST 10-40 spare parts also needs to be replaced, supported by a support value of 67% and 88% confidence. If replacing MST spare parts 10-40, the possibility of CB 8-20 spare parts also needs to be replaced, supported by a Support value of 58% and 100% Confidence. If replacing a 16-50 CB spare part, the possibility of a CB 8-20 spare part also needs to be replaced, supported by a Support value of 50% and a 100% Confidence. If replacing a WSS 12 spare part, the possibility of a WSS 10 spare part that might also need to be replaced, is supported by a Support value of 50% and a 100% Confidence.